IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS (SDGs) MENGENAI CLIMATE ACTION OLEH SECRETARIAT OF THE PACIFIC REGIONAL ENVIRONMENT PROGRAMME (SPREP) DI NEGARA KIRIBATI - Nia Anggreni; Umi Oktyari Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The South Pacific region, especially the country of Kiribati, is threatened with drowning due to rising sea levels due to the effects of climate change. The Secretariat of the Pacific Regional Environment (SPREP) is healing the fears of countries in the South Pacific to overcome and be useful for handling the impacts of climate change. SPREP's vision and mission are in line with SDGs Point 13. The purpose of this research is to find out the role played by SPREP in implementing (SDGs) point 13 regarding climate action in the country of Kiribati. This study uses a pluralism perspective, with a country analysis level. This study also uses international organization theory. The method used in this study is a qualitative method with data collection techniques using literature and various literature that refers to books, journals, and sites on the internet. The results of the study show that SPREP has implemented SDGs Point 13 regarding climate action in Negra Kiribati, evidence of SPREP's role in implementing this can be seen by the running of several programs. Some of these programs have succeeded in implementing the 3 targets of SDGs Point 13, this can be seen by the implementation of the collaboration between SPREP and the Kiwa Initiative in assisting funding for countries in the South Pacific region which will make programs related to sustainable development, especially the environment and handling impacts climate change which is in line with target 1. Target 2 is implemented by looking at the progress of COSPPac and ROK-PI ClipS, these two programs make it very easy for the public as well as researchers to see very complete reports regarding rainfall, sea conditions, and matters related to climate those in the South Pacific especially in Kiribati that way national planning will be easier to make. Target 3 can be seen from the implementation of COSPPac and ROK-PI ClipS where these two programs will facilitate access to information related to sea and climate conditions so that countries in the Pacific will receive early warning regarding the impacts of climate change that will occur. Keywords: Climate Change, SPREP, SDGs 13, Kiribati